La poesia di Menzogna e sortilegio. Leopardi, Saba, Penna e l’antidoto alla tragedia - Cerneaz, Sara (L’ospite ingrato, 2025)
Poetry in Menzogna e sortilegio adds to the complex textuality of the first novel by Elsa Morante, acting both the textual thresholds, as the dedications Alla favola and Ai personaggi, and inside the text itself, as in the farewell Canto per il gatto Alvaro. This paper aims to read the writer’s verses as part of an intertextual dialogue with Alibi (1958) – which has a relevant genetic relation with Menzogna e sortilegio, as shown by the philological study of Morante’s manuscripts – and in relation to the melodramatic instances of the novel, already assessed by Morante’s critics, in order to help defining the textuality of Menzogna e sortilegio and the poetics of Elsa Morante herself, who often voiced her foundational and passionate relationship with poetry.